ANALYSIS OF STUDENT ERRORS IN WORKING ON HOTS QUESTIONS FOR ALGEBRA MATERIALS ON WATSON"™S CRITERIA BASED ON GENDER - Wulandari, Ayu; Hadi, Windia (Jurnal Pendidikan Matematika dan IPA, 2023)
This study aims to determine what errors students made in working on algebraic Higher Order Thinking Skill (HOTS) questions based on gender. This type of research method uses qualitative research methods. Data collection techniques in the form of essay test instruments, student interviews, and triangulation were used to test the validity of the data. This research was conducted on tenth-grade high school students in Jakarta by taking research subjects, namely those with high and low abilities. The results showed that the indicators of errors made by high-ability male students occurred in indicators of inaropriate procedures, errors other than the 7 criteria (not solving the problem), missing conclusions, and indirect manipulation. Meanwhile, women made mistakes on error indicators other than the 7 criteria (not solving the problem), incorrect procedures, and missing conclusions. As for the error indicator, the male student with low ability made an error on the error indicator other than the 7 criteria (not solving the problem), but the procedure indicator did not. Meanwhile, female students made mistakes on indicators other than the 7 criteria (not solving the problem), incorrect data, incorrect procedures, missing conclusions, indirect manipulation, and hierarchical problems.